Forward Error Correction for Fast Streaming with Open-Source Components - John Reynolds (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2015)
The mechanisms that provide streaming functionality are complex and far from perfect. Reliability in transmission depends upon the underlying protocols chosen for implementation. There are two main networking protocols for data transmission: TCP and UDP. TCP guarantees the arrival of data at the receiver, whereas UDP does not. Forward Error Correction is based on a technology called “erasure coding”, and can be used to mitigate data loss experienced when using UDP. This paper describes in detail the development of a video streaming library making use of the UDP transport protocol in order to test and further explore network based Forward Error Correction erasure codes.